ANALYSIS OF SUSTAINABILITY REPORTS FROM AGRICULTURE AND FORESTRY-RELATED ORGANIZATIONS LISTED ON THE B3 ISE, ACCORDING TO THE GRI FRAMEWORK (REMUNOM, 2026)
Sustainability has become increasingly important in the corporate context as companies are pressured to adopt good practices that meet social and environmental expectations. In this scenario, the adoption of sustainability reports, aligned with the standards of the Global Reporting Initiative (GRI), has emerged as an essential tool for communicating corporate performance. The objective of this article is to analyze the sustainability reports of agribusiness companies listed on the Corporate Sustainability Index (ISE) of B3, verifying their adherence to GRI standards, with a focus on the economic, social, and environmental impacts generated by these organizations. The research is qualitative and descriptive in nature, using comparative analysis to examine the sustainability reports provided by the companies for the period from 2020 to 2022. The sample consisted of companies in the agricultural production chain that use raw materials from agriculture, livestock, and forestry. Based on the analysis of these companies, it was possible to highlight the growing importance of transparency and the evolution in the disclosure of such information, including the creation of a ranking of organizations that maintain the highest compliance with the global standards of GRI.